Elucidating the formation and active state of Cu co-catalysts for photocatalytic hydrogen evolution. Issue 38 (20th September 2021) - Schubert, Jasmin S.; Kalantari, Leila; Lechner, Andreas; Giesriegl, Ariane; Nandan, Sreejith P.; Alaya, Pablo; Kashiwaya, Shun; Sauer, Markus; Foelske, Annette; Rosen, Johanna; Blaha, Peter; Cherevan, Alexey; et al.
Abstract : Calcination of Cu/TiO2 is detrimental to its photocatalytic HER performance. We relate this to heat-activated Cu diffusion into the TiO2 lattice, which decreases accessibility of the Cu sites on the surface and generates charge recombination centers. Abstract : The design of active and selective co-catalysts constitutes one of the major challenges in developing heterogeneous photocatalysts for energy conversion applications. This work provides a comprehensive insight into thermally induced bottom-up generation and transformation of a series of promising Cu-based co-catalysts. We demonstrate that the volcano-type HER profile as a function of calcination temperature is independent of the type of the Cu precursor but is affected by changes in oxidation state and location of the copper species. Supported by DFT modeling, our data suggest that low temperature (<200 °C) treatments facilitate electronic communication between the Cu species and TiO2, which allows for a more efficient charge utilization and maximum HER rates. In contrast, higher temperatures (>200 °C) do not affect the Cu oxidation state, but induce a gradual, temperature-dependent surface-to-bulk diffusion of Cu, which results in interstitial, tetra-coordinated Cu + species. The disappearance of Cu from the surface and the introduction of new defect states is associated with a drop in HER performance. This work examines electronic and structural effects that are in control of the photocatalytic activity and can be transferred to other systems for further advancing photocatalysis.